High-resolution analysis of the initiation of deep convection forced by boundary-layer processes - Khodayar Pardo, Samiro (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2015)
The initiation of atmospheric convection is investigated using the synergy of different instruments. The impact of increased spatial data resolution on the detection of the initiation of deep convection is analysed, and a methodology is developed to determine the likelihood of deep convection over flat and complex terrains. Intensive Observation Periods (IOPs) are used from the Convective Storm Initiation Project (CSIP), and the Convective and Orographically-Induced Precipitation Study (COPS).